LEGO MINDSTORMS NXT-G Programming Guide, Second Edition - Kelly, James Floyd (Apress, 2012)
Welcome to the second edition of LEGO MINDSTORMS NXT-G Programming Guide. Since the release of the first edition in 2007, the LEGO MINDSTORMS robotics kit has exploded in popularity and continues to find its way into the hands of newcomers. The first NXT robotics kit was released in late 2006 to rave reviews, and NXT-G, the graphical software used to program robots, was a huge hit. By following along with some built-in tutorials, users of the new robotics kit were given the basics of the software and set free to design and create some of the strangest, silliest, useful, and/or most unique robots you’d ever imagine. But programming with the NXT-G software wasn’t easy for everyone to understand – some took to it immediately and others struggled to understand basic concepts. I wrote the first edition using simple language, a familiar tone, and short chapters to try and not overwhelm those new to programming with NXT-G. I avoided technical jargon where I could and introduced readers to my version of pseudo code that I felt would help new NXT-G programmers better understand how to formulate an idea and turn it into a real NXT-G program. The feedback I received from the book was overwhelming, especially from teachers and parents who found themselves also needing to learn NXT-G to work and enjoy robot building and programming with their students or children. In late 2009 a new version of the NXT robotics kit was release – NXT 2.0. And with the new kit came an update to the NXT-G software. Luckily, the majority of the software looked and worked just like the 1.0 version released back in 2006. There were new features and tools, yes, but the basics of how NXT-G works and looks stayed the same. Students, teachers, and parents, familiar with NXT-G 1.0, would have very little difficulty figuring out NXT-G 2.0. But what about those completely new to the NXT robotics kit?